2019
DOI: 10.3390/ani9010023
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Strategies Before and at Mixing: The Effect on Sow Aggression and Behavior

Abstract: Simple SummarySows in domestic settings are often mixed into new groups of animals, resulting in the need to form hierarchies, causing aggression and related stress. Restrictively fed gestating sows are unlikely to be sated, and are more likely to view food as a limited resource and to be frustrated and aggressive. Creating satiety in sows as they are mixed may be a simple method to reduce mixing aggression. This experiment assessed the provision of different diets; a standard diet (CON) or high (HI) volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A growing number of studies have indicated that animal welfare is impaired in many conditions and should be improved ( Sapkota et al., 2016 ; Greenwood et al., 2019 ; Maes et al., 2019 ). Gestating sows tend to suffer insufficient satiety frequently due to feed restriction ( De Leeuw et al., 2005 ; Schneider et al., 2007 ; de Leeuw et al., 2008 ; Greenwood et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have indicated that animal welfare is impaired in many conditions and should be improved ( Sapkota et al., 2016 ; Greenwood et al., 2019 ; Maes et al., 2019 ). Gestating sows tend to suffer insufficient satiety frequently due to feed restriction ( De Leeuw et al., 2005 ; Schneider et al., 2007 ; de Leeuw et al., 2008 ; Greenwood et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have indicated that animal welfare is impaired in many conditions and should be improved ( Sapkota et al., 2016 ; Greenwood et al., 2019 ; Maes et al., 2019 ). Gestating sows tend to suffer insufficient satiety frequently due to feed restriction ( De Leeuw et al., 2005 ; Schneider et al., 2007 ; de Leeuw et al., 2008 ; Greenwood et al., 2019 ). The insufficient satiety of sows can be reflected by their stereotypical behaviors (often referred to as sham-chewing behavior, sniffing behavior and licking behavior) and physical activities (standing, lying, sitting, kneeling and position change) ( de Leeuw et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 In response, sows may become increasingly frustrated, developing stereotypic behaviors that result in aggressive interactions towards pen mates. [2][3][4] Social hierarchy establishment elicits intense aggression that is generally resolved 2 days after initial mixing, whereas aggression related to pen resources is more chronic 5 and can occur throughout gestation, 1 particularly when sow satiety is not reached. Sow satiety is often measured by assessing self-directed or substratedirected stereotypic behavior.…”
Section: Résumé -Stratégies D'alimentation Pour Améliorer La Satiété ...mentioning
confidence: 99%
“…Some also suggest that increasing feed allowance for up to 4 days after mixing is beneficial in reducing fights, although there is limited research available that supports this recommendation. 5…”
Section: Feed Allowancementioning
confidence: 99%
“…Cinta Senese pigs and their crosses on pasture, preferred to conduct their activities in groups most of the time, particularly during morning hours [34]. In groups, dominance relationships between animals are established with subordinate animals having limited access to resources such as feed, water, preferred space, and receiving most of the aggressions [164].…”
Section: Social Behaviormentioning
confidence: 99%